src/HOL/Hyperreal/Series.thy
 author huffman Sun, 24 Sep 2006 03:38:36 +0200 changeset 20688 690d866a165d parent 20552 2c31dd358c21 child 20689 4950e45442b8 permissions -rw-r--r--
change definitions from SOME to THE
```
(*  Title       : Series.thy
Author      : Jacques D. Fleuriot
Copyright   : 1998  University of Cambridge

Converted to Isar and polished by lcp
Converted to setsum and polished yet more by TNN
*)

theory Series
imports SEQ Lim
begin

declare atLeastLessThan_iff[iff]
declare setsum_op_ivl_Suc[simp]

definition
sums  :: "(nat => real) => real => bool"     (infixr "sums" 80)
"f sums s = (%n. setsum f {0..<n}) ----> s"

summable :: "(nat=>real) => bool"
"summable f = (\<exists>s. f sums s)"

suminf   :: "(nat=>real) => real"
"suminf f = (THE s. f sums s)"

syntax
"_suminf" :: "idt => real => real"    ("\<Sum>_. _" [0, 10] 10)
translations
"\<Sum>i. b" == "suminf (%i. b)"

lemma sumr_diff_mult_const:
"setsum f {0..<n} - (real n*r) = setsum (%i. f i - r) {0..<n::nat}"

lemma real_setsum_nat_ivl_bounded:
"(!!p. p < n \<Longrightarrow> f(p) \<le> K)
\<Longrightarrow> setsum f {0..<n::nat} \<le> real n * K"
using setsum_bounded[where A = "{0..<n}"]
by (auto simp:real_of_nat_def)

(* Generalize from real to some algebraic structure? *)
lemma sumr_minus_one_realpow_zero [simp]:
"(\<Sum>i=0..<2*n. (-1) ^ Suc i) = (0::real)"
by (induct "n", auto)

(* FIXME this is an awful lemma! *)
lemma sumr_one_lb_realpow_zero [simp]:
"(\<Sum>n=Suc 0..<n. f(n) * (0::real) ^ n) = 0"
apply (induct "n")
apply (case_tac [2] "n", auto)
done

lemma sumr_group:
"(\<Sum>m=0..<n::nat. setsum f {m * k ..< m*k + k}) = setsum f {0 ..< n * k}"
apply (subgoal_tac "k = 0 | 0 < k", auto)
apply (induct "n")
done

(* FIXME generalize? *)
lemma sumr_offset:
"(\<Sum>m=0..<n::nat. f(m+k)::real) = setsum f {0..<n+k} - setsum f {0..<k}"
by (induct "n", auto)

lemma sumr_offset2:
"\<forall>f. (\<Sum>m=0..<n::nat. f(m+k)::real) = setsum f {0..<n+k} - setsum f {0..<k}"
by (induct "n", auto)

lemma sumr_offset3:
"setsum f {0::nat..<n+k} = (\<Sum>m=0..<n. f (m+k)::real) + setsum f {0..<k}"

lemma sumr_offset4:
"\<forall>n f. setsum f {0::nat..<n+k} =
(\<Sum>m=0..<n. f (m+k)::real) + setsum f {0..<k}"

(*
lemma sumr_from_1_from_0: "0 < n ==>
(\<Sum>n=Suc 0 ..< Suc n. if even(n) then 0 else
((- 1) ^ ((n - (Suc 0)) div 2))/(real (fact n))) * a ^ n =
(\<Sum>n=0..<Suc n. if even(n) then 0 else
((- 1) ^ ((n - (Suc 0)) div 2))/(real (fact n))) * a ^ n"
by (rule_tac n1 = 1 in sumr_split_add [THEN subst], auto)
*)

subsection{* Infinite Sums, by the Properties of Limits*}

(*----------------------
suminf is the sum
---------------------*)
lemma sums_summable: "f sums l ==> summable f"
by (simp add: sums_def summable_def, blast)

lemma summable_sums: "summable f ==> f sums (suminf f)"
apply (simp add: summable_def suminf_def sums_def)
apply (blast intro: theI LIMSEQ_unique)
done

lemma summable_sumr_LIMSEQ_suminf:
"summable f ==> (%n. setsum f {0..<n}) ----> (suminf f)"
by (rule summable_sums [unfolded sums_def])

(*-------------------
sum is unique
------------------*)
lemma sums_unique: "f sums s ==> (s = suminf f)"
apply (frule sums_summable [THEN summable_sums])
apply (auto intro!: LIMSEQ_unique simp add: sums_def)
done

lemma sums_split_initial_segment: "f sums s ==>
(%n. f(n + k)) sums (s - (SUM i = 0..< k. f i))"
apply (unfold sums_def);
apply (rule LIMSEQ_diff_const)
apply (rule LIMSEQ_ignore_initial_segment)
apply assumption
done

lemma summable_ignore_initial_segment: "summable f ==>
summable (%n. f(n + k))"
apply (unfold summable_def)
apply (auto intro: sums_split_initial_segment)
done

lemma suminf_minus_initial_segment: "summable f ==>
suminf f = s ==> suminf (%n. f(n + k)) = s - (SUM i = 0..< k. f i)"
apply (frule summable_ignore_initial_segment)
apply (rule sums_unique [THEN sym])
apply (frule summable_sums)
apply (rule sums_split_initial_segment)
apply auto
done

lemma suminf_split_initial_segment: "summable f ==>
suminf f = (SUM i = 0..< k. f i) + suminf (%n. f(n + k))"

lemma series_zero:
"(\<forall>m. n \<le> m --> f(m) = 0) ==> f sums (setsum f {0..<n})"
apply (simp add: sums_def LIMSEQ_def diff_minus[symmetric], safe)
apply (rule_tac x = n in exI)
done

lemma sums_zero: "(%n. 0) sums 0";
apply (unfold sums_def);
apply simp;
apply (rule LIMSEQ_const);
done;

lemma summable_zero: "summable (%n. 0)";
apply (rule sums_summable);
apply (rule sums_zero);
done;

lemma suminf_zero: "suminf (%n. 0) = 0";
apply (rule sym);
apply (rule sums_unique);
apply (rule sums_zero);
done;

lemma sums_mult: "f sums a ==> (%n. c * f n) sums (c * a)"
by (auto simp add: sums_def setsum_right_distrib [symmetric]
intro!: LIMSEQ_mult intro: LIMSEQ_const)

lemma summable_mult: "summable f ==> summable (%n. c * f n)";
apply (unfold summable_def);
apply (auto intro: sums_mult);
done;

lemma suminf_mult: "summable f ==> suminf (%n. c * f n) = c * suminf f";
apply (rule sym);
apply (rule sums_unique);
apply (rule sums_mult);
apply (erule summable_sums);
done;

lemma sums_mult2: "f sums a ==> (%n. f n * c) sums (a * c)"
apply (subst mult_commute)
apply (subst mult_commute);back;
apply (erule sums_mult)
done

lemma summable_mult2: "summable f ==> summable (%n. f n * c)"
apply (unfold summable_def)
apply (auto intro: sums_mult2)
done

lemma suminf_mult2: "summable f ==> suminf f * c = (\<Sum>n. f n * c)"
by (auto intro!: sums_unique sums_mult summable_sums simp add: mult_commute)

lemma sums_divide: "f sums a ==> (%n. (f n)/c) sums (a/c)"
by (simp add: real_divide_def sums_mult mult_commute [of _ "inverse c"])

lemma summable_divide: "summable f ==> summable (%n. (f n) / c)";
apply (unfold summable_def);
apply (auto intro: sums_divide);
done;

lemma suminf_divide: "summable f ==> suminf (%n. (f n) / c) = (suminf f) / c";
apply (rule sym);
apply (rule sums_unique);
apply (rule sums_divide);
apply (erule summable_sums);
done;

lemma sums_add: "[| x sums x0; y sums y0 |] ==> (%n. x n + y n) sums (x0+y0)"

lemma summable_add: "summable f ==> summable g ==> summable (%x. f x + g x)";
apply (unfold summable_def);
apply clarify;
apply (rule exI);
apply assumption;
done;

"[| summable f; summable g |]
==> suminf f + suminf g  = (\<Sum>n. f n + g n)"
by (auto intro!: sums_add sums_unique summable_sums)

lemma sums_diff: "[| x sums x0; y sums y0 |] ==> (%n. x n - y n) sums (x0-y0)"
by (auto simp add: sums_def setsum_subtractf intro: LIMSEQ_diff)

lemma summable_diff: "summable f ==> summable g ==> summable (%x. f x - g x)";
apply (unfold summable_def);
apply clarify;
apply (rule exI);
apply (erule sums_diff);
apply assumption;
done;

lemma suminf_diff:
"[| summable f; summable g |]
==> suminf f - suminf g  = (\<Sum>n. f n - g n)"
by (auto intro!: sums_diff sums_unique summable_sums)

lemma sums_minus: "f sums s ==> (%x. - f x) sums (- s)";
by (simp add: sums_def setsum_negf LIMSEQ_minus);

lemma summable_minus: "summable f ==> summable (%x. - f x)";
by (auto simp add: summable_def intro: sums_minus);

lemma suminf_minus: "summable f ==> suminf (%x. - f x) = - (suminf f)";
apply (rule sym);
apply (rule sums_unique);
apply (rule sums_minus);
apply (erule summable_sums);
done;

lemma sums_group:
"[|summable f; 0 < k |] ==> (%n. setsum f {n*k..<n*k+k}) sums (suminf f)"
apply (drule summable_sums)
apply (auto simp add: sums_def LIMSEQ_def sumr_group)
apply (drule_tac x = r in spec, safe)
apply (rule_tac x = no in exI, safe)
apply (drule_tac x = "n*k" in spec)
apply (auto dest!: not_leE)
apply (drule_tac j = no in less_le_trans, auto)
done

lemma sumr_pos_lt_pair_lemma:
"[|\<forall>d. - f (n + (d + d)) < (f (Suc (n + (d + d))) :: real) |]
==> setsum f {0..<n+Suc(Suc 0)} \<le> setsum f {0..<Suc(Suc 0) * Suc no + n}"
apply (induct "no", auto)
apply (drule_tac x = "Suc no" in spec)
done

lemma sumr_pos_lt_pair:
"[|summable f;
\<forall>d. 0 < (f(n + (Suc(Suc 0) * d))) + f(n + ((Suc(Suc 0) * d) + 1))|]
==> setsum f {0..<n} < suminf f"
apply (drule summable_sums)
apply (auto simp add: sums_def LIMSEQ_def)
apply (drule_tac x = "f (n) + f (n + 1)" in spec)
--{*legacy proof: not necessarily better!*}
apply (rule_tac [2] ccontr, drule_tac [2] linorder_not_less [THEN iffD1])
apply (frule_tac [2] no=no in sumr_pos_lt_pair_lemma)
apply (drule_tac x = 0 in spec, simp)
apply (rotate_tac 1, drule_tac x = "Suc (Suc 0) * (Suc no) + n" in spec)
apply (safe, simp)
apply (subgoal_tac "suminf f + (f (n) + f (n + 1)) \<le>
setsum f {0 ..< Suc (Suc 0) * (Suc no) + n}")
apply (rule_tac [2] y = "setsum f {0..<n+ Suc (Suc 0)}" in order_trans)
prefer 3 apply assumption
apply (rule_tac [2] y = "setsum f {0..<n} + (f (n) + f (n + 1))" in order_trans)
apply simp_all
done

text{*A summable series of positive terms has limit that is at least as
great as any partial sum.*}

lemma series_pos_le:
"[| summable f; \<forall>m \<ge> n. 0 \<le> f(m) |] ==> setsum f {0..<n} \<le> suminf f"
apply (drule summable_sums)
apply (cut_tac k = "setsum f {0..<n}" in LIMSEQ_const)
apply (erule LIMSEQ_le, blast)
apply (rule_tac x = n in exI, clarify)
apply (rule setsum_mono2)
apply auto
done

lemma series_pos_less:
"[| summable f; \<forall>m \<ge> n. 0 < f(m) |] ==> setsum f {0..<n} < suminf f"
apply (rule_tac y = "setsum f {0..<Suc n}" in order_less_le_trans)
apply (rule_tac [2] series_pos_le, auto)
apply (drule_tac x = m in spec, auto)
done

text{*Sum of a geometric progression.*}

lemmas sumr_geometric = geometric_sum [where 'a = real]

lemma geometric_sums: "abs(x) < 1 ==> (%n. x ^ n) sums (1/(1 - x))"
apply (case_tac "x = 1")
apply (auto dest!: LIMSEQ_rabs_realpow_zero2
apply (subgoal_tac "1 / (1 + -x) = 0/ (x - 1) + - 1/ (x - 1) ")
apply (erule ssubst)
apply (auto intro: LIMSEQ_const simp add: diff_minus minus_divide_right LIMSEQ_rabs_realpow_zero2)
done

text{*Cauchy-type criterion for convergence of series (c.f. Harrison)*}

lemma summable_convergent_sumr_iff:
"summable f = convergent (%n. setsum f {0..<n})"
by (simp add: summable_def sums_def convergent_def)

lemma summable_Cauchy:
"summable f =
(\<forall>e > 0. \<exists>N. \<forall>m \<ge> N. \<forall>n. abs(setsum f {m..<n}) < e)"
apply (simp only: summable_convergent_sumr_iff Cauchy_convergent_iff [symmetric] Cauchy_def diff_minus [symmetric], safe)
apply (drule spec, drule (1) mp)
apply (erule exE, rule_tac x="M" in exI, clarify)
apply (rule_tac x="m" and y="n" in linorder_le_cases)
apply (frule (1) order_trans)
apply (drule_tac x="n" in spec, drule (1) mp)
apply (drule_tac x="m" in spec, drule (1) mp)
apply simp
apply (drule spec, drule (1) mp)
apply (erule exE, rule_tac x="N" in exI, clarify)
apply (rule_tac x="m" and y="n" in linorder_le_cases)
apply (subst norm_minus_commute)
done

text{*Comparison test*}

lemma summable_comparison_test:
"[| \<exists>N. \<forall>n \<ge> N. abs(f n) \<le> g n; summable g |] ==> summable f"
apply (drule spec, auto)
apply (rule_tac x = "N + Na" in exI, auto)
apply (rotate_tac 2)
apply (drule_tac x = m in spec)
apply (auto, rotate_tac 2, drule_tac x = n in spec)
apply (rule_tac y = "\<Sum>k=m..<n. abs(f k)" in order_le_less_trans)
apply (rule setsum_abs)
apply (rule_tac y = "setsum g {m..<n}" in order_le_less_trans)
apply (auto intro: setsum_mono simp add: abs_interval_iff)
done

lemma summable_rabs_comparison_test:
"[| \<exists>N. \<forall>n \<ge> N. abs(f n) \<le> g n; summable g |]
==> summable (%k. abs (f k))"
apply (rule summable_comparison_test)
apply (auto)
done

text{*Limit comparison property for series (c.f. jrh)*}

lemma summable_le:
"[|\<forall>n. f n \<le> g n; summable f; summable g |] ==> suminf f \<le> suminf g"
apply (drule summable_sums)+
apply (auto intro!: LIMSEQ_le simp add: sums_def)
apply (rule exI)
apply (auto intro!: setsum_mono)
done

lemma summable_le2:
"[|\<forall>n. abs(f n) \<le> g n; summable g |]
==> summable f & suminf f \<le> suminf g"
apply (auto intro: summable_comparison_test intro!: summable_le)
done

(* specialisation for the common 0 case *)
lemma suminf_0_le:
fixes f::"nat\<Rightarrow>real"
assumes gt0: "\<forall>n. 0 \<le> f n" and sm: "summable f"
shows "0 \<le> suminf f"
proof -
let ?g = "(\<lambda>n. (0::real))"
from gt0 have "\<forall>n. ?g n \<le> f n" by simp
moreover have "summable ?g" by (rule summable_zero)
moreover from sm have "summable f" .
ultimately have "suminf ?g \<le> suminf f" by (rule summable_le)
then show "0 \<le> suminf f" by (simp add: suminf_zero)
qed

text{*Absolute convergence imples normal convergence*}
lemma summable_rabs_cancel: "summable (%n. abs (f n)) ==> summable f"
apply (drule spec, auto)
apply (rule_tac x = N in exI, auto)
apply (drule spec, auto)
apply (rule_tac y = "\<Sum>n=m..<n. abs(f n)" in order_le_less_trans)
apply (auto)
done

text{*Absolute convergence of series*}
lemma summable_rabs:
"summable (%n. abs (f n)) ==> abs(suminf f) \<le> (\<Sum>n. abs(f n))"
by (auto intro: LIMSEQ_le LIMSEQ_imp_rabs summable_rabs_cancel summable_sumr_LIMSEQ_suminf)

subsection{* The Ratio Test*}

lemma rabs_ratiotest_lemma: "[| c \<le> 0; abs x \<le> c * abs y |] ==> x = (0::real)"
apply (drule order_le_imp_less_or_eq, auto)
apply (subgoal_tac "0 \<le> c * abs y")
done

lemma le_Suc_ex: "(k::nat) \<le> l ==> (\<exists>n. l = k + n)"
apply (drule le_imp_less_or_eq)
done

lemma le_Suc_ex_iff: "((k::nat) \<le> l) = (\<exists>n. l = k + n)"

(*All this trouble just to get 0<c *)
lemma ratio_test_lemma2:
"[| \<forall>n \<ge> N. abs(f(Suc n)) \<le> c*abs(f n) |]
==> 0 < c | summable f"
apply (simp (no_asm) add: linorder_not_le [symmetric])
apply (safe, subgoal_tac "\<forall>n. N < n --> f (n) = 0")
prefer 2
apply clarify
apply(erule_tac x = "n - 1" in allE)
apply (blast intro: rabs_ratiotest_lemma)
apply (rule_tac x = "Suc N" in exI, clarify)
apply(simp cong:setsum_ivl_cong)
done

lemma ratio_test:
"[| c < 1; \<forall>n \<ge> N. abs(f(Suc n)) \<le> c*abs(f n) |]
==> summable f"
apply (frule ratio_test_lemma2, auto)
apply (rule_tac g = "%n. (abs (f N) / (c ^ N))*c ^ n"
in summable_comparison_test)
apply (rule_tac x = N in exI, safe)
apply (drule le_Suc_ex_iff [THEN iffD1])
apply (induct_tac "na", auto)
apply (rule_tac y = "c*abs (f (N + n))" in order_trans)
apply (auto intro: mult_right_mono simp add: summable_def)
apply (rule_tac x = "abs (f N) * (1/ (1 - c)) / (c ^ N)" in exI)
apply (rule sums_divide)
apply (rule sums_mult)
apply (auto intro!: geometric_sums)
done

text{*Differentiation of finite sum*}

lemma DERIV_sumr [rule_format (no_asm)]:
"(\<forall>r. m \<le> r & r < (m + n) --> DERIV (%x. f r x) x :> (f' r x))
--> DERIV (%x. \<Sum>n=m..<n::nat. f n x) x :> (\<Sum>r=m..<n. f' r x)"
apply (induct "n")